2001
DOI: 10.1046/j.1464-5491.2001.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hospital inpatient length of stay for patients with diabetes

Abstract: The introduction of a ward-based diabetes nurse advisor was associated with significant reductions in length of stay in inpatients with diabetes. Since this study was not a randomized study, other factors may have contributed to this change. However, the consistency of the reduction across specialities suggests the post itself had an important effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…Their involvement shortens patient stay and improves safety [22][23][24][25]. The Diabetes Specialist Team should be informed as soon as possible during the acute phase, but this will depend on local circumstances.…”
Section: The Involvement Of Diabetes Specialist Teamsmentioning
confidence: 99%
“…Their involvement shortens patient stay and improves safety [22][23][24][25]. The Diabetes Specialist Team should be informed as soon as possible during the acute phase, but this will depend on local circumstances.…”
Section: The Involvement Of Diabetes Specialist Teamsmentioning
confidence: 99%
“…Westert and colleagues show that the variation in LOS is larger between hospitals than within them [10]. Cavan and colleagues showed that length of stay in hospitals for patients with diabetes was significantly reduced when a ward-based diabetes nurse adviser was introduced [11]. This indicates that variables other than the case-mix can explain LOS variation.…”
Section: Length Of Stay In Hospitalmentioning
confidence: 99%
“…Various authors have attempted to determine the factors that predict or modify the length of hospitalization in patients with pathologies prevalent in our setting, such as chronic obstructive pulmonary disease [1] , heart failure [2] , diabetes mellitus [3] , acute myocardial infarction [4] and pneumonia.…”
Section: Introductionmentioning
confidence: 99%